1992
DOI: 10.1104/pp.98.3.971
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Lipoxygenase Isoforms in Senescing Carnation Petals

Abstract: A membrane-associated lipoxygenase and a soluble lipoxygenase have been identified in camation (Dianthus caryophyllus L. cv Reve) petals. Treatments of microsomal membranes by nonionic or zwitterionic detergents indicated that lipoxygenase is tightly bound to the membranes. By phase separation in Triton X-114, microsomal lipoxygenase can be identified in part as an integral membrane protein. Soluble lipoxygenase had an optimum pH range of 4.9 to 5.8, whereas microsomal lipoxygenase exhibited maximum activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Even though LOX is often proposed to be responsible for peroxidative damage to membrane lipids during aging and senescence, its role is far from clear. LOX activity increases during senescence of rose petals [17], daylily petals [18], carnation petals [19], and pea foliage [20], but clearly decreases during soybean seed aging [21], soybean cotyledon senescence [22] or in detached wheat and rye leaves [23]. In a previous study [24], we showed that in potato tubers stored at 20 jC, LOX activity and the total HPO content decreased during aging, even during the period after 120 days when membrane integrity dropped drastically.…”
Section: Introductionmentioning
confidence: 81%
“…Even though LOX is often proposed to be responsible for peroxidative damage to membrane lipids during aging and senescence, its role is far from clear. LOX activity increases during senescence of rose petals [17], daylily petals [18], carnation petals [19], and pea foliage [20], but clearly decreases during soybean seed aging [21], soybean cotyledon senescence [22] or in detached wheat and rye leaves [23]. In a previous study [24], we showed that in potato tubers stored at 20 jC, LOX activity and the total HPO content decreased during aging, even during the period after 120 days when membrane integrity dropped drastically.…”
Section: Introductionmentioning
confidence: 81%
“…Besides its cytosolic localization, LOX have been detected in different types of cellular membranes [11][12][13][14][15][16][17][18][19][20] and, in some cases, appear to be tightly bound to reconstituted membranes [12,14,[17][18][19][20], or present in spe cific organelles (chloroplasts or mitochondria) [12][13][14][15][16]. In particular, membrane-bound LOX, found in microsomal vesicles from tomato fruit and senescing carnation petals have been partially characterized [18,19]' Both utilize linoleic acid as substrate, have a pH optimum near to 6.0 and are distinguishable from their soluble counterpart. Membrane fractionation studies indicate that the tomato fruit enzyme is associated with thylakoid membranes [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, they have been shown in vacuoles [11], mitochondria [12][13][14][15], chloroplasts [12,[15][16][17] and microsomal membranes [12,13,[18][19][20]. Hitherto, their presence in the plasmalemma of plant cells has not been conclusively demonstrated, albeit in a recent paper a plasma membrane-associated LOX has been de scribed [21].…”
Section: Introductionmentioning
confidence: 99%
“…No sistema vegetal, as lipoxigenases ocorrem em várias partes da planta, desempenhando funções em processos tais como: crescimento e desenvolvimento 1 , senescência 3 , reserva vegetativa 4 , germinação de sementes 5 , resposta a ferimento 6 e resistência a insetos e patógenos 7 . Os principais substratos de lipoxigenases, em plantas superiores, são os ácidos linoléico e linolênico 8 .…”
Section: Introductionunclassified